Auto-centered development and indigenous technics: Slaheddine el-Amami and Tunisian delinking. Issue 6 (19th September 2019) - Ajl, Max
ABSTRACT: Until his early death in 1985, at age 51, the Tunisian agronomist Slaheddine el-Amami carried out a path-breaking research program at what was then the Centre de Recherche et de Génie Rural. He wrote technical studies ranging from the agricultural capacities of the unjustly-marked-as-barren Kerkennah Islands, to possibilities for drip irrigation, to attempts to quantify the energy use of Tunisian agriculture, to a wide-ranging investigation of indigenous hydraulic systems. There is little explicit mention in this work of a then-dominant strand of heterodox Arab and Third Worldist social science – the emphasis on delinking, or removal from Western commodity, technical and financial flows. Yet through an examination of his work in the context of the delinking paradigm, as put forth by scholars like Samir Amin, Fawzy Mansour and Mohamed Dowidar, I show the use and need for independent agronomic expertise to be deployed within analytical paradigms such as delinking, forged by heterodox political economists. Through delinking, countries could proceed on a path of auto-centered development. The possibility and time frame of delinking is necessarily a socio-technical question linked to indigenous capacities, technical and natural, and the social relations with which they are woven. It is also a question of creating and mobilizing a surplus in the agricultural sector. Through examining Amami's life's work, I show the use and need for interdisciplinary methods and research programs, which must braid the social and natural sciences – if not simply take threads from each to create a holistic knowledge – in order to arrive at appropriate developmental programs. Such knowledge and programs were appropriate in that they offered ways of working agriculture without capital-intense inputs – thus resolving rather than aggravating current account imbalances and labor surpluses. They also relied on a decentralization of planning, based on the skills and knowledges of the direct producers. In analyzing such knowledge, systematized in the work of Amami, I will also show how moving from underdevelopment to development requires a mélange of knowledges. Crucial and neglected are those knowledges which have been developed to inform sustainable ways of living on land-bases, in order to produce the rural surplus which is the sine qua non of a successful move beyond developmental malaise in the Global South. I will then link this to the International Assessment of Agricultural Knowledge, Science and Technology for Development (IAASTD) Synthesis Report, showing this paradigm's continuing relevance.